Reflections on the Spirituality of Three Black Gay Men - Lawrence O. Bryant; E. Paulette Isaac-Savage; Lorenzo Bowman (Adult Education Research Conference, 2014)
Spirituality is important in the lives of African Americans. Not surprising then, it is significant for Black gay men, as members of the African American community. In this paper we discuss five themes that emerged from an analysis of three autoethnographies.